2011
DOI: 10.1093/ndt/gfr576
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of nephrin-Neph3 gene pair is synergistically activated by WT1 and NF- B and silenced by DNA methylation

Abstract: Background. Nephrin and Neph3 are homologous molecules expressed in the podocyte slit diaphragms that are essential for normal glomerular ultrafiltration. Nephrin and Neph3 genes form a bidirectional gene pair suggesting that they may share key features in their regulation. We investigated if nephrin and Neph3 genes have similar mechanisms in their transcriptional regulation focussing on transcription factor Wilms' tumour 1 (WT1) and nuclear factor-jB (NF-jB) and DNA methylation. Methods. Transcriptional regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…2A). The nephrin gene NPHS1 has been shown to be an NF-B target gene (25). Indeed, NPHS1 mRNA expression was induced by TNF␣, and knockdown of ACTN4 abolished TNF␣-mediated induction of NPHS1 mRNA.…”
Section: Actn4 Is Required For Nf-b Transcriptional Activity-ourmentioning
confidence: 99%
“…2A). The nephrin gene NPHS1 has been shown to be an NF-B target gene (25). Indeed, NPHS1 mRNA expression was induced by TNF␣, and knockdown of ACTN4 abolished TNF␣-mediated induction of NPHS1 mRNA.…”
Section: Actn4 Is Required For Nf-b Transcriptional Activity-ourmentioning
confidence: 99%
“…Recent evidence indicates that WT1 and NF-kB physically interact with the promoters for two homologous proteins, nephrin and Neph3 (filtrin), expressed in the podocyte slit diaphragm, and they cooperatively regulate the expression of nephrin and Neph3. 46 Thus, these results present a plausible explanation that the reduction of nephrin expression occurring in the Tak1 Δ/Δ kidney might be caused by decreased WT1 expression and failed NF-kB activation resulting from Tak1 deletion. Null mutations in the nephrin gene nphs1 cause congenital nephrotic syndrome of the Finnish type characterized by podocyte foot process effacement and absence of slit diaphragms.…”
Section: Discussionmentioning
confidence: 69%
“…Although it has been previously known that WT1, 42,43 Sp1, 44 and Snail 45 are implicated in the regulation of Nphs1 expression, recent studies have shown that NF-kB and WT1 cooperatively regulate Nphs1 transcription. 46 Here, we show that podocyte-specific deletion of Tak1 in mice resulted in high incidence of perinatal lethality, proteinuria, delayed glomerulogenesis, and reduced expression of WT1 and nephrin in the podocytes. Tak1 deletion in podocytes caused disruption of the podocyte architecture and foot process effacement.…”
mentioning
confidence: 72%
“…It was hypothesized by Bechtel et al [11] that fibroblast activation in fibrotic kidney disease is the result of epigenetic alterations, more precisely DNA-methylation, which renders them terminally activated. It is becoming clear that DNA-methylation, in addition to cancer pathologies, also plays an important role in renal pathologies, since independent investigators found that aberrant DNA-methylation is associated with inflammation [12,13] , development of renal fibrosis [11,[14][15][16], and that it occurs during ischemia in transplantation [17,18] . Importantly, aberrant DNA-methylation is thought to influence allograft survival, since advanced donor age, differentiation, and polarization of immune cells as well as ischemia are associated with alterations in the DNA-methylation pattern [5,19,20] .…”
Section: Introductionmentioning
confidence: 99%